Supernova neutrino burst detection with the Deep Underground Neutrino Experiment - Abi,B; Acciarri,R; Acero,MA; Adamov,G; Adams,D; Adinolfi,M; Ahmad,Z; Ahmed,J; Alion,T; Monsalve,SA; Alt,C; Anderson,J; et al. (European Physical Journal C: Particles and Fields, 2021)
The Deep Underground Neutrino Experiment (DUNE), a 40-kton underground liquid argon time projection chamber experiment, will be sensitive to the electron-neutrino flavor component of the burst of neutrinos expected from the next Galactic core-collapse supernova. Such an observation will bring unique insight into the astrophysics of core collapse as well as into the properties of neutrinos. The general capabilities of DUNE for neutrino detection in the relevant few- to few-tens-of-MeV neutrino energy range will be described. As an example, DUNE’s ability to constrain the νe spectral parameters of the neutrino burst will be considered.